2022
DOI: 10.1186/s13075-022-02740-x
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive profile of chemokines in the peripheral blood and vascular tissue of patients with Takayasu arteritis

Abstract: Background Takayasu arteritis (TAK) is a chronic granulomatous large vessel vasculitis with multiple immune cells involved. Chemokines play critical roles in recruitment and activation of immune cells. This study aimed to investigate chemokine profile in the peripheral blood and vascular tissue of patients with TAK. Methods A total of 58 patients with TAK and 53 healthy controls were enrolled. Chemokine array assay was performed in five patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…Another study evaluated serum chemokines such as CXCL10, CXCL13, CCL5, and CXCL8 in TAK patients, but none showed signi cant differences between active disease and remission 29 . In line with these ndings, Kong et al also found no differences in the levels of CCL5, CXCL16, CXCL11, and IL-16 between patients with active disease and those in remission 30 .…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Another study evaluated serum chemokines such as CXCL10, CXCL13, CCL5, and CXCL8 in TAK patients, but none showed signi cant differences between active disease and remission 29 . In line with these ndings, Kong et al also found no differences in the levels of CCL5, CXCL16, CXCL11, and IL-16 between patients with active disease and those in remission 30 .…”
Section: Discussionmentioning
confidence: 69%
“…Persistently high serum CCL22 levels have been described in TAK patients compared to HC 30 , and a further increase in its levels was observed even after therapy for TAK. Our study, however, was the rst to describe signi cant differences between active disease and remission regarding CCL22 serum levels in TAK.…”
Section: Discussionmentioning
confidence: 98%
“…Pathway enrichment analyses, both Reactome and KEGG pathway, revealed that cytokines and chemokines are playing a critical role in the pathogenesis of TA. Evaluated chemokines in Frontiers in Genetics frontiersin.org vessel tissues of TA with immunofluorescence and immunohistochemistry staining and identified CCL22, RANTES, CXCL16, CXCL11, and IL-16 as the major chemokines recruiting immune cells in the vascular tissue of patients with TA (Kong et al, 2022). As to cytokines and its receptor, found out increased expression of IL-1R2 genes in PBMCs of patients with TA.…”
Section: Discussionmentioning
confidence: 99%
“…Further validating these chemokines in 20 TAK patients and 20 healthy controls, five chemokines (CCL22, RANTES, CXCL11, CXCL16, IL-16) were confirmed to be elevated in TAK. However, none of these cytokines were associated with ESR or CRP or were significantly different between active and inactive TAK in a separate cohort of 25 patients with TAK [ 146 ].…”
Section: Circulating Biomarkers Of Disease Activity In Takmentioning
confidence: 99%